Predators and livestock reduce bird nest survival in intensive Mediterranean farmland - Beja, Pedro (2015)
High nest predation is one of the factors potentially driving farmland bird declines, particularly in the case of ground-nesting species. Accordingly, recent calls have been made to address predation in agri-environment schemes, but this is hindered by limited understanding of how processes operating at different scales affect predation patterns and how additional factors such as livestock trampling contribute to reduced nest survival. Using an artificial nest experiment, we assessed how field management, landscape composition and configuration, and the abundance of potential avian predators and mammalian carnivores affected predation and trampling rates in grassland fields (pastures and fallows) embedded in intensive Mediterranean farmland. Mean predation and trampling rates per field were 0.18±0.23 SD and 0.12±0.17 SD, respectively. However, there was strong spatial variation, with high nest losses (>50 %) occurring in about one quarter of the fields. Variation in failure rates was mainly related to livestock grazing and predator abundances, while the effects of landscape context were negligible. Predation and trampling rates were highest in fields with short swards. Predation rate was positively related to the abundance of Egyptian mongooses and dogs. To increase nest survival, agri-environment schemes designed for ground-nesting birds should contribute for maintaining low stocking density. Further evaluation is required on the need for controlling populations of fastexpanding generalist predators such as mongooses.